2014
DOI: 10.1111/anec.12212
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Fragmented QRS Complexes for Identifying Left Ventricular Hypertrophy in Patients with Hypertension

Abstract: fQRS is a common electrocardiographic phenomenon in patients with hypertension. Although the diagnostic value for LVH is limited, the presence of fQRS on ECG is associated with a higher risk for worse LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…1 They used the left ventricular ejection fraction, septum and posterior wall thickness, gradients, strain pattern, and systolic pulmonary artery pressure as echocardiographic parameters. 3 In the present study of Açıkgöz, et al there are significantly higher mean and peak gradients in patients with fQRS group. In a study which includes patients with hypertension and normal coronary angiogram, LVMI was significantly higher in the patients with fQRS than that of patients who did not have fQRS on ECG.…”
supporting
confidence: 44%
“…1 They used the left ventricular ejection fraction, septum and posterior wall thickness, gradients, strain pattern, and systolic pulmonary artery pressure as echocardiographic parameters. 3 In the present study of Açıkgöz, et al there are significantly higher mean and peak gradients in patients with fQRS group. In a study which includes patients with hypertension and normal coronary angiogram, LVMI was significantly higher in the patients with fQRS than that of patients who did not have fQRS on ECG.…”
supporting
confidence: 44%
“…However, its importance in patients with hypertension is not well described, particularly in patients without LVH. It has been shown that the frequency of fQRS is significantly higher in patients with LVH compared with absence of LVH in individuals with hypertension . This finding may indicate the higher fibrotic burden in patients with LVH.…”
Section: Discussionmentioning
confidence: 96%
“…This finding also indicates the importance of higher fibrotic burden in myocardium and electrocardiographic risk assessment of persons with hypertension in the absence of LVH. The higher frequency of fQRS in the hypertensive population seems to be mainly related to LVH, and CAD‐related fibrosis is one of the most powerful predictors of presence of fQRS on ECG . Hence, we excluded all patients with LVH to avoid its effect on fQRS frequency.…”
Section: Discussionmentioning
confidence: 99%
“…18 Additionally, in the absence of CAD, left ventricular hypertrophy and increased left ventricle mass are associated with higher frequency of fQRS in patients with normal left ventricular ejection fraction. 19-21 Therefore, in our study, in addition to vascular diseases, we excluded patients with lower ejection fraction, moderate to severe valvular diseases and evidence of left ventricular hypertrophy to identify the exact predictive value of fQRS in terms of presence of CAD and CAD severity.…”
Section: Discussionmentioning
confidence: 99%